Architectural competitions as an instrument for heritage protection: the dynamics of competition taxonomy. Issue 4 (1st October 2016) - Mikelsone, Ilze
Abstract: Various concepts of preserving the cultural and historical environment of the Historical centre of Riga have been documented within the last century period, including the international status as item No. 852 on the UNESCO World heritage list. The Riga Historical Centre Preservation and Protection Law was created as one of the mechanisms for the preservation of the status, which, among other notions, makes the procedure of architectural competitions mandatory. The territory, being part of the list, contains listings that it should consider in terms of value. Under such context the competition not only determines the competition for the best and serves as formal instrument for hindering hasty or inappropriate development, but also is public interpretation of the contemporary architectural values in contra dictionary aspects. The purpose is to analyse the structure of competition procedure instrument and relation to the specifics of the heritage and contemporary challenges . The study uses 75 competitions briefs and jury protocols proceeding in period 2004–2014, in the territory of urban heritage. The results demonstrate taxonomy1 of systemic listings of architectural properties followed by expert voting form as the main mechanism for results.